Perspectives of Clinical Instructors of Nursing Student Competences in Acute and Critical Care - Retnaningsih, Dwi (Fakultas Ilmu-ilmu Kesehatan, 2024)
Nursing students must be competent in providing acute and critical care. This study investigated the perspectives of clinical instructors on these competencies in challenging nursing environments. Ten clinical instructors from the Regional Hospital of Semarang City, Central Java, Indonesia, participated in this study to observe students during their clinical practice in acute and critical care. Qualitative data was collected between May and December 2020. Face-to-face and virtual in-depth interviews lasted 30 to 40 minutes per informant. Data validity was ensured by member verification, which involved participants reviewing the recorded interviews. The nursing competency perspectives were divided into nine themes: (1) addressing biological, psychological, social, and spiritual needs; (2) involving families in patient care; (3) integrating attitudes, morals, and ethics; (4) developing communication skills; (5) working in multidisciplinary teams and complementary therapies; (6) effectively managing emergencies effectively; (7) recognizing and addressing spiritual aspects; (8) developing critical thinking and technology mastery; and (9) improving quality. This study’s findings serve as a valuable reference and guide for refining nursing student competencies in acute and critical care and creating assessment instruments.